Allelic deletions in the long arm of chromosome 12 identify sites of candidate tumor suppressor genes in male germ cell tumors. - Murty, V V (1992)
Human male germ cell tumors (GCTs) result from malignant transformation of premeiotic or early meiotic germ cells and exhibit embryonal-like differentiation of the three germinal layers. The genetic basis of origin and expression of differentiated phenotypes by GCTs are poorly understood. Our recent cytogenetic analysis of a large series of GCTs has shown that two chromosome 12 abnormalities, an isochromosome for the short arm [i(12p)] and deletions in the long arm [del(12q)], characterize these tumors, which led us to suggest that the deletions represent loss of one or more candidate tumor suppressor genes whose products regulate the normal proliferation of the spermatogonial stem cells. We undertook a molecular mapping of the deletions by comparing germ-line and tumor genotypes of eight polymorphic loci in paired normal/tumor DNA samples from 45 GCT patients. Analysis of loss of constitutional heterozygosity at these loci revealed two regions of frequent loss (> 40%), one at 12q13 and the other at 12q22, identifying the sites of the postulated tumor suppressor genes. One tumor (no. 143A) exhibited a homozygous deletion of a region of 12q22, which included the MGF gene. The KIT and MGF genes have been shown to play key roles in embryonal and postnatal development of germ cells; therefore, we evaluated their expression by Northern blot analysis in a panel of three GCT cell lines and 24 fresh GCT biopsies. Deregulated expression of MGF and KIT, which was discordant between seminomatous and nonseminomatous lesions, was observed.